THE ASSESSMENT OF THREE PROCESS AREAS IN MATURITY LEVEL 2 CMMI-DEV 1.2 FRAMEWORK ON SMALL INDEPENDENT SOFTWARE VENDOR IN INDONESIA (CASE STUDY: INOVASIA) - Kautsarina Kautsarina (Pusbindiklat - LIPI, 2011)
This research was conducted to get a snapshot of the utilization of the Capability Maturity Model Integration (CMMI) framework in a small ISV, with Inovasia as a case study, by assessing three process areas of level 2 as a ﬁ rst step in achieving software development activities in a timely, meets the needs of users, and within the budget provided. Software process improvement implemented in CMMI for Development model version 1.2 by using Management Information System Interim Maturity Evaluation (MISIME) as a tool to diagnose the maturity level of an ISV. This study generated value of current maturity level of ISV and software process improvement recom-mendations that can be done by the ISV.